Effectiveness of a Family Support Intervention on Caregiving Burden in Family of Elderly Patients With Cognitive Decline After the COVID-19 Lockdown - Cravello, Luca; Martini, Eleonora; Viti, Niccolò; Campanello, Cristina; Assogna, Francesca; Perotta, Daniele (Frontiers in Psychiatry, 2021)
Background: the COVID-19 pandemic had a great impact on patients with cognitive decline or dementia. The lockdown period may exacerbate behavioral disorders and worsen distress of caregivers. The aim of this study is to evaluate the effectiveness of a family support intervention on the effects of COVID-19 lockdown. Methods: we recruited patients whose related caregivers attended a course for family members of patients with cognitive decline or dementia. Data on cognitive decline, neuropsychiatric symptoms and functional status were collected before the course, the caregiving burden was evaluated at the end of the course. After COVID-19 lockdown a phone interview was made to compare neuropsychiatric symptoms, functional status, and caregiver’s burden with previous evaluation. Results: after COVID-19 lockdown there was a reduction of neuropsychiatric symptoms, but the difference did not reach statistical significance. Despite a worsen of patients’ functional status, the caregivers’ burden decreased significantly probably due to the positive effect of the family support intervention. Conclusions: our study demonstrated that a complete family support intervention for caregivers of patients with cognitive decline and other type of dementia can reduce neuropsychiatric symptoms and the burden of care even in a particular negative period such as the COVID-19 lockdown.